Reproductive factors and lung cancer risk among women in the Singapore Breast Cancer Screening Project. Issue 3 (December 2015) - Tan, Hui Shan; Tan, Min-Han; Chow, Khuan Yew; Chay, Wen Yee; Lim, Wei-Yen
Highlights: Increasing evidence suggests a role of hormonal factors in lung cancer development. We analysed 28, 222 women from the Singapore Breast Cancer Screening Project. Associations between reproductive variables and lung cancer were investigated. Inverse association was observed between parity and total lung cancer risk. Abstract: Objectives: A growing body of literature suggests that female hormones play a role in lung cancer risk. Our study aims to examine the relationship between reproductive factors and lung cancer incidence in a large prospectively enrolled cohort in Singapore. Materials and Methods: Multivariate Cox proportional hazard regression models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) of lung cancer for each exposure, adjusting for smoking, age at entry, ethnicity and body mass index. Results: Among 28, 222 women aged 50–64 years enrolled in the Singapore Breast Cancer Screening Project from October 1994 to February 1997, we identified 311 incident lung cancer cases (253 in non-smokers) over an average of 15.8 years of follow-up to 31 December 2011. Higher parity was associated with decreased lung cancer risk. Compared with nulliparous women, those with 1–2, 3–4, and ≥5 deliveries had a hazard ratio (HR) of 0.56, 0.55 and 0.45, respectively ( P trend  < 0.01). This association was observed in both smokers and non-smokers, and in both adenocarcinomas and non-adenocarcinomas. Reproductive period, breastfeeding, oral contraceptive and hormone replacement therapy use did not seem to influence the risk of getting lung cancer. Conclusion: Our findings add to the existing evidence that parous women have a lower lung cancer risk than nulliparous women.